Monocytopenia, monocyte morphological anomalies and hyperinflammation characterise severe COVID‐19 in type 2 diabetes - Fawaz Alzaid; Jean‐Baptiste Julla; Marc Diedisheim; Charline Potier; Louis Potier; Gilberto Velho; Bénédicte Gaborit; Philippe Manivet; Stéphane Germain; Tiphaine Vidal‐Trecan; Ronan Roussel; Jean‐Pierre Riveline; et al. (EMBO Molecular Medicine)
Abstract Early in the COVID‐19 pandemic, type 2 diabetes (T2D) was marked as a risk factor for severe disease and mortality. Inflammation is central to the aetiology of both conditions where variations in immune responses can mitigate or aggravate disease course. Identifying at‐risk groups based on immunoinflammatory signatures is valuable in directing personalised care and developing potential targets for precision therapy. This observational study characterised immunophenotypic variation associated with COVID‐19 severity in T2D. Broad‐spectrum immunophenotyping quantified 15 leucocyte populations in peripheral circulation from a cohort of 45 hospitalised COVID‐19 patients with and without T2D. Lymphocytopenia and specific loss of cytotoxic CD8+ lymphocytes were associated with severe COVID‐19 and requirement for intensive care in both non‐diabetic and T2D patients. A morphological anomaly of increased monocyte size and monocytopenia restricted to classical CD14Hi CD16− monocytes was specifically associated with severe COVID‐19 in patients with T2D requiring intensive care. Increased expression of inflammatory markers reminiscent of the type 1 interferon pathway (IL6, IL8, CCL2, INFB1) underlaid the immunophenotype associated with T2D. These immunophenotypic and hyperinflammatory changes may contribute to increased voracity of COVID‐19 in T2D. These findings allow precise identification of T2D patients with severe COVID‐19 as well as provide evidence that the type 1 interferon pathway may be an actionable therapeutic target for future studies.